In-hospital major bleeding in patients with acute coronary syndrome medically treated with dual anti-platelet therapy: Associated factors and impact on mortality - Sun, Yihong; Feng, Lin; Li, Xian; Wang, Zhe; Gao, Runlin; Wu, Yangfeng (Frontiers in Cardiovascular Medicine, 2022)
Background Major bleeding and associated factors in patients with acute coronary syndrome (ACS) on dual anti-platelet therapy (DAPT) but no access to revascularization is of highest clinical interest but relevant studies were sparse. Methods We analyzed data of 19186 patients on DAPT after ACS with no access to revascularization from CPACS-3 cohort, which was recruited from 2011 to 2014. Major bleeding included intracranial hemorrhage, clinical significant bleeding or bleeding that requiring blood transfusion. Factors associated with in-hospital major bleeding were assessed using Poisson regressions with generalized estimating equations to account for clustering effect. Results A total of 75 (0.39%) patients experienced major bleeding during hospitalization. Among subtypes of ACS, 0.65% patients with STEMI, 0.33% with NSTEMI and 0.13% with unstable angina had in-hospital major bleeding (p<0.001). The patients who experienced major bleeding had longer length of stay (median 12 days vs 9 days, P=0.011) and higher all cause in-hospital death rate (22.7% vs 3.6%, P<0.001).Multivariable analysis showed age advancing (RR=1.52 , 95%CI: 1.13, 2.05), impaired renal function (RR=1.79, 95%CI: 1.10, 2.92), use of fibrinolysis (RR=2.93, 95%CI: 1.55, 5.56), and severe diseases other than cardiovascular and renal disease (RR=5.56, 95%CI: 1.10, 28.07) were associated with increased but use of ACEI/ARB (RR=0.54, 95%CI: 0.36, 0.81) were associated with decreased risk of major bleedings. The multivariable models showed good predictive accuracy with AUC of 0.788 (95%CI: 0.734,0.841). Conclusions Among ACS patients on DAPT, age advancing, impaired renal function, thrombolysis treatment, and severe comorbidities were independently associated with higher risk of in-hospital major bleeding.